2019
DOI: 10.1016/j.jsams.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and oxygenation responses of local ischemia and systemic hypoxia during arm cycling repeated sprints

Abstract: Objectives: The purpose of this study was to investigate the acute vascular and oxygenation responses to repeated sprint exercise during arm cycling with either blood flow restriction (BFR) or systemic hypoxia alone or in combination. Design: The study design was a single-blinded repeated-measures assessment of four conditions with two levels of normobaric hypoxia (400 m and 3800 m) and two levels of BFR (0% and 45% of total occlusion). Methods: Sixteen active participants (eleven men and five women; mean ± SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…Additionally, the magnitude and location (conduit, resistance, capillary vessel) of the vascular adaptations depend on the intensity, volume of exposure, and mode of training (Green et al, 2011). Indeed, when combining BFR and/or systemic hypoxia with high-intensity exercise, a robust stimulus is placed on the vascular mechanisms (Willis et al, 2018, 2019a,b). These different methods of systemic and local hypoxia along with the differing underlying mechanisms (metabolic vasodilation and vascular resistance, respectively) can provide a great stimulus alone or in combination to alter vascular conductance and blood flow regulation.…”
Section: Blood Flow Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the magnitude and location (conduit, resistance, capillary vessel) of the vascular adaptations depend on the intensity, volume of exposure, and mode of training (Green et al, 2011). Indeed, when combining BFR and/or systemic hypoxia with high-intensity exercise, a robust stimulus is placed on the vascular mechanisms (Willis et al, 2018, 2019a,b). These different methods of systemic and local hypoxia along with the differing underlying mechanisms (metabolic vasodilation and vascular resistance, respectively) can provide a great stimulus alone or in combination to alter vascular conductance and blood flow regulation.…”
Section: Blood Flow Restrictionmentioning
confidence: 99%
“…When high-intensity exercise is performed with BFR, in addition to a strong deoxygenation due to the localized hypoxia, there is a larger increase in the changes in blood perfusion in both legs and arms (vastus lateralis and biceps brachii, respectively) (Willis et al, 2018, 2019b). High-intensity exercise with BFR is able to create a potent stimulus via vascular resistance and altered vasodilatory responses, and was shown to be more robust than with systemic hypoxia in both legs and arms (Peyrard et al, 2019; Willis et al, 2019a,b). In fact, during high-intensity exercise with a certain level of BFR, an additional stimulus of systemic hypoxia is likely blunted (Willis et al, 2019a).…”
Section: High-intensity Exercise With Blood Flow Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present RSE (10 s:20 s) likely induces a high anaerobic contribution as shown by previous research (Girard et al, 2011; Bishop, 2012). It was reported that RSE induces different acute hemodynamic responses when performed to exhaustion either in systemic hypoxia or with BFR (Willis et al, 2017, 2018) with greater changes in total hemoglobin present during BFR conditions (Willis et al, 2019). Both from a mechanistic and a practical point of view, it is of interest to investigate if IPC and HPC would also induce greater changes in the hemodynamic response of deoxygenation and total hemoglobin during RSE.…”
Section: Methodsmentioning
confidence: 99%
“…Considering these differences, it is uncertain if aerobic exercise with BFR will elicit similar physiological responses in the upper-body as those observed in the lower-body. Two groups [70,71] have reported acute physiological responses to supramaximal arm cranking with BFR.…”
Section: Introductionmentioning
confidence: 99%